Coffee Consumption and Non-alcoholic Fatty Liver Disease: An Umbrella Review and a Systematic Review and Meta-analysis - Kositamongkol, Chayanis; Kanchanasurakit, Sukrit; Auttamalang, Chiraphong; Inchai, Nutkamon; Kabkaew, Thanatchaporn; Kitpark, Sarunporn; Chaiyakunapruk, Nathorn; Duangjai, Acharaporn; Saokaew, Surasak; Phisalprapa, Pochamana (Frontiers in Pharmacology, 2021)
Background: The effects of coffee consumption on hepatic outcomes are controversial. This study investigated the associations between coffee consumption and the incidence of non-alcoholic fatty liver disease (NAFLD) in the general population, and reduction of liver fibrosis among patients with NAFLD. Methods: The study consisted of 2 parts: an umbrella review, and a systematic review and meta-analysis (SRMA). The searches for each part were performed separately using PubMed, EMBASE, Cochrane, Scopus and CINAHL databases. All articles published up to September 2021 were reviewed. To be eligible, studies for the umbrella review were required to report outcomes that compared the risks of NAFLD in the general population and/or liver fibrosis in patients with NAFLD who did and did not drink coffee. Our SRMA included primary studies reporting the effects of coffee consumption on NAFLD-related outcomes. The outcomes were pooled using a random effects model and reported in both qualitative and quantitative terms (pooled risk ratio, odds ratio and weighted mean difference). Results: We identified 4 published SRMAs during the umbrella review. Most studies showed the general population who regularly drank coffee were significantly associated with a lower NAFLD incidence than those who did not. Our SRMA included 9 studies on the effects of coffee consumption on NAFLD incidence. Pooled data from 147 875 subjects showed that coffee consumption was not associated with a lower NAFLD incidence in the general population. The between-study heterogeneity was high (I2, 72%–85%). Interestingly, among patients with NAFLD (5 studies; n = 3752), coffee consumption was significantly associated with a reduction in liver fibrosis (odds ratio, 0.67; 95% CI, 0.55 to 0.80; I2, 3%). There were no differences in the coffee consumption of the general population and of those with NAFLD (4 studies; n = 19 482) or by patients with no/mild liver fibrosis and those with significant fibrosis (4 studies; n = 3331). Conclusions: There are contrasting results on the effects of coffee on NAFLD prevention in the general population. Benefits of coffee consumption on liver fibrosis were seen among patients with NAFLD.